[Pi]-loaded rhenium complexes : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Chemistry at Massey University, Palmerston North, New Zealand - Steedman, Andrew (Massey University, 2000)
A range of rhenium(VII) tris(imido) complexes, XRe(NR)3 (X=Me3SiO, R=Ar'; X=Cl, R=Ar', mes, Ar), have been synthesized either from [ReO4]-, RNH2 (R=Ar', mes, Ar), Et3N and Me3SiCl or Re(NR)2Cl3(py), RNH2 (R=Ar', Ar) and Et3N. An X-ray crystal structure of Me3SiORe(NAr')3 and ClRe(NAr)3 showed a slightly bent Re-N-C angle (158.8(5)° and 168.8(7)° respectively) and short Re-N distances (1.749(6)Å and 1.758(7)Å). Mixed tris(imido) complexes, ClRe(NR)2(NR') (R=Ar, R'=Ar, p-tol; R=Ar, R'=Ar, p-FC6H4, p-NO2C6H4, p-tol, AMP, o-ClC6H4, m-ClC6H4, o-tBuC6H4) have been synthesized from Re(NR)2Cl3(py) (R=Ar', Ar), R'NH2 (R'= Ar, p-tol, Ar', p-FC6H4, p-NO2C6H4, AMP, o-ClC6H4, m-ClC6H4, o-tBuC6H4) and Et3N. An X-ray crystal structure of ClRe(NAr)2(NAr') showed near linear Re-N-C angles (165(2)-172.5(19)°) and short Re-N distances (1.70(2)-1.766(19)Å). The crystal structure of ClRe(NAr)2(N-o-tBu) showed 2 near linear Re-N-Ar angles (172.4(2)° and 171.2(2)°) and one bent Re-N-o-tBu angle (160.8(2)°). Intermolecular imido ligand exchange was shown to occur slowly at room temperature between NAr' and Nmes. However, exchange between NAr' and NAr required heating to 60°C for exchange to occur. A chiral tetrahedral complex, ClRe(NAr')(NAr)(N-o-tBu), was synthesized from Re(NAr')(NAr)Cl3(py), o-tBuC6H4NH2 and Et3N. Alkyl/aryl derivatives of the mixed tris(imido) complexes, R"Re(NR)2(NR') (R=Ar', Ar, R'-Ar', Ar, R"=Me, p-tol, CH2Ph), have been synthesized from ClRe(NR)2(NR') (R=Ar, R'=Ar'; R=Ar', R'=Ar) and the Grignard, R"MgX (R"=Me, p-tol, X=Br; R"=CH2Ph, X=Cl). An X-ray crystal structure of MeRe(NAr)2(NAr') showed near linear Re-N-C angles (168.5(3)-171.2(3)°) and short Re-N lengths (1.753(4)-1.763(4)Å). The Re-N-Ar' angle was found to be ~ 10° larger than those found for tris(Ar'-imido) Re(VII) tetrahedral complexes. An oxo-bridging species, [Re(NAr)2(p-tol)(µ-O)]2, was isolated presumably from the hydrolysis of p-tolRe(NAr)3. The crystal structure of [Re(NAr)2(p-tol)(µ-O)]2 showed the rhenium atoms to be in a distorted square pyramidal geometry, as indicated by the Re-O bond distances (1.948(2) and 1.985(3)Å). Bis(imido) complexes, Re(NR)(NR')Cl3(py) (R=Ar', R'=Ar', Ar; R=R'=Ar), were synthesized from ClRe(NR)2(NR') (R=Ar', R'=Ar', Ar; R=Ar, R'=Ar', Ar) and pyHCl. An X-ray crystal structure of Re(NAr')2Cl3(py) showed near linear Re-N-C angles (171.8(12) and 174.4(3)°) and short Re-N distances (1.734(18) and 1.760(14)Å). The Cl ligands in the cis positions to the imido ligands are bent away from the imido ligands at an angle of 166.10(19)°. Amido complexes, p-tolNHRe(NR)(NR')(NR"), have been synthesized from ClRe(NR)(NR')(NR") (R=R'=Ar, R"=Ar, o-tBu; R=Ar, R'=Ar', R"=o-tBu) and LiNHp-tol. An X-ray crystal structure of p-tolNHRe(NAr)3 showed a bent Re-NH-C angle (129.6(3)°) typical of amido nitrogens. A range of Re(V) tris(imido) complexes, [Re(NR)2(NR')]- (R=R'=Ar'; R=Ar, R'=Ar', Ar, o-tBu), have been synthesized from XRe(NR)2(NR') (X=Me3SiO, Cl) and elemental sodium. These anions were found to be very sensitive both in solution and as solids. An X-ray crystal structure of [Re(NAr')3]- showed the complex to possess a 2-fold axis of symmetry through one of the imido ligands. The counter ion was found to be Na+ with 6 coordinated molecules of thf. The anions were found to react with ClSnMe3 and ClAuPPh3 to form Re-Sn (Me3SnRe(NAr)2(NR), R=Ar', Ar, o-tBu) and Re-Au (Ph3PAuRe(NR)2(NR'), R=R'=Ar'; R=Ar, R'=Ar', Ar) complexes respectively. The crystal structure of Me3SnRe(NAr)3 and Me3SnRe(NAr)2(NAr') showed near linear Re-N-C angles (170.2(5)-172.9(2)°) and short Re-N distances (1.752(6)-1.779(3)Å). Rhenium(VI) dimeric complexes were synthesized from the anion, [Re(NR)2(NR')]- (R=R'=Ar'; R=Ar, R'=Ar', Ar, o-tBu) and ferrocenium, [Cp2Fe]+. Both Re2(NAr')6 and Re2(NAr)4(NAr')2 contain bridging imido ligands, while Re2(NAr)6 and Re2(NAr)4(N-o-tBu)2 contain only terminal imido ligands, as indicated by proton NMR. An X-ray crystal structure of [Re(NAr')2(µ-NAr')]2 showed slightly bent terminal imido angles (156.2(3) to 168.8(3)°), short Re-N(terminal) distances (1.750(4) to 1.763(3)Å) and typical Re-N(bridging) distances of 1.951-1.959(4)Å. The average Re-Re distance of 2.735(4)Å indicates a weak metal-metal interaction. The crystal structure of Re2(NAr)6 showed the complex adopts an ethane-like geometry with the imido ligands arranged in a staggered orientation. The Re-Re bond lies on a crystallographic S6 axis. A Re(VII) cation, [Re(NAr)3]+, is implicated on the basis of formation of a ferrocene complex, (C5H5)Fe(C5H4)Re(NAr)3.
Keywords: Rhenium; Ligands; Transition metal complexes; Fields of Research::250000 Chemical Sciences